The Influence of Work Motivation and Leadership Style on The Performance of Educators in Formal Early Childhood Education in Rancasari District, Bandung City - Sari, Helen Purnama; Putra, Ivan Gumilar Sambas (Universitas Pamulang, 2023)
Educational institutions that are effective or successful when supported by quality human resources and the performance of human resources greatly influence the success of a company without exception. The object of this study is to analyze the effect of work motivation and leadership style on the performance of educators. This research was conducted at the Formal PAUD in Rancasari District, Bandung City. Data was collected through the results of sampling with a self-administered questionnaire filled out by 113 respondents. The research method used is descriptive and verification methods with a quantitative approach. The data analysis technique in this study used multiple linear regression analysis. In this study, researchers used IBM SPSS Statistics as a means of processing SPSS version 28 data. The results showed that work motivation has a positive and significant effect on the performance of educators and leadership style has a positive and significant effect on the performance of educators.